2016
DOI: 10.1111/jicd.12208
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic effect of Centella asiatica Linn and asiatic acid on arecoline‐induced fibrosis in human buccal fibroblasts

Abstract: CA and AA can be used as antifibrotic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…AA shows promising potential for the treatment of periodontitis. Further, AA exhibited an antifibrotic effect in primary human buccal fibroblasts induced by arecoline (Adtani et al, 2017 ). AA showed salvage of fibroblast morphology mediating inhibition of transforming growth factor-β1, collagen 1 type 2, and collagen 3.…”
Section: Asiatic Acid In Periodontitismentioning
confidence: 99%
“…AA shows promising potential for the treatment of periodontitis. Further, AA exhibited an antifibrotic effect in primary human buccal fibroblasts induced by arecoline (Adtani et al, 2017 ). AA showed salvage of fibroblast morphology mediating inhibition of transforming growth factor-β1, collagen 1 type 2, and collagen 3.…”
Section: Asiatic Acid In Periodontitismentioning
confidence: 99%
“…Previous studies suggested that AA possessed a wide range of pharmacological properties, including antihepatofibric, neuroprotective, anti-inflammatory, anti-diabetic and antitumor activities ( 9 ). As for antitumor effect, AA was reported to induce apoptosis in hepatic and breast cancer cell lines and other tumor cells ( 10 , 11 ). The efficacy of AA was possibly attributed to the inhibition of nuclear factor-κB, p38 mitogen-activated protein kinase and extracellular signal-regulated kinase, as well as the change of Bcl-2 and caspase family proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, ROS administered in the form of subcutaneously injected HOCl was used to induce SSc in a mouse model that has been widely used since 2009 (22). Preliminary experiments in SSc mice were also performed by assessing the effects of different doses of HOCl as described previously (7,20,(28)(29)(30), 300 µl was chosen as the optimal dose. This model mimicked the diffuse cutaneous form of human SSc, which exhibited increased collagen deposition, inflammatory infiltration in the lungs and autoimmune activation compared with control mice.…”
Section: Discussionmentioning
confidence: 99%